NORTHWESTERN COLCHIS IN THE REIGN OF PACORUS: Received: 28th April 2026, Revised: 04th May 2026, 05th May 2026, Accepted: 07th May 2026, Date of Publication: 08th May 2026 - Kakhaber Pipia (PEOPLE: International Journal of Social Sciences, 2026)
At the beginning of the 2nd century AD, five new political entities emerged along the Eastern Black Sea coast, within the territory of historical Colchis. According to Flavius Arrian (ca. 95–175 AD), the southernmost of these was the kingdom of the Macrones and Heniochi. The Laz controlled the central part of Colchis up to the River Egristskali (modern Ghalidzga), while to their north lay the “kingdoms” of the Apsilae, Abasgoi, and Sanigae. This was the political configuration of the eastern Black Sea region when Pacorus, king of the Laz, appeared on the historical stage. He received his authority from Antoninus Pius (138–161 AD). Given the geopolitical situation in the Black Sea basin, the Laz–Roman alliance strengthened during the reign of Antoninus Pius. As the artifacts discovered in northwestern Colchis indicate, significant transformations took place in the eastern Black Sea region during Pacorus’ rule. This is confirmed by a silver cup with a Greek inscription unearthed in 2005 in an ancient grave at the village of Achmarda in the modern Gagra district. The inscription reads: Ἐγὼ Πάκουρος ὁ βασιλεὺς τοῖς ἀ|μνοῖς ἔδωκα -“I, King Pacorus, have given [this] to my sheep.” The inscription shows that by the mid-2nd century, the Laz king Pacorus had brought the Sanigae confederation under his authority. Naturally, this implies that he had already incorporated the smaller political groups of the Apsilae and Abasgoi into his kingdom earlier. Thus, Pacorus, the contemporary of Antoninus Pius, whose authority at the time of his accession extended only as far as the River Ghalidzga, succeeded within a short period in incorporating the confederations of the Apsilae, Abasgoi, and Sanigae. He laid the foundation for a powerful western Georgian polity whose northwestern boundary stretched to the River Akheountos (modern Shakhe). The consequences of Pacorus’ activities and the establishment of a unified state in western Georgia are reflected in the Geography of Ptolemy (ca. 100–170 AD). Unlike Arrian, Ptolemy no longer mentions the Apsilae, Abasgoi, or Sanigae in northwestern Colchis. He accurately reflects the new political reality and, throughout the entire eastern Black Sea region—from the province of Cappadocia to Sarmatia—refers to only one political unit: Colchis. It is clear that Ptolemy uses the term “Colchis” out of older tradition, and that in his time it corresponds to the later “Lazica.”